Development and Application of a Prioritization Tool for Animal Health Surveillance Activities in Ireland - Clarke, AnneMarie; More, Simon J.; Maher, James W.; Byrne, Andrew W.; Horan, Michael; Barrett, Damien (Frontiers in Veterinary Science, 2020)
Decisions around animal health management by stakeholders are often subject to resource limitation, therefore prioritisation processes are required to evaluate whether effort is attributed appropriately. The objectives of this study were to develop and apply a surveillance prioritisation process for animal health surveillance activities in Ireland. An exploratory sequential mixed research methods design was utilised. A prioritisation tool was developed for surveillance activities and implemented over two phases. During the first phase, a survey was conducted which asked stakeholders to prioritise diseases/conditions by importance for Irish agriculture. In the second phase, experts identified the most important surveillance objectives, and allocated resources to the activities that they considered would best meet the surveillance objectives, for each disease/condition. This study developed a process and an accompanying user-friendly practical tool for animal disease surveillance prioritisation which could be utilised by other competent authorities/governments. Antimicrobial resistance and bovine tuberculosis were ranked top of the endemic diseases/conditions in the Irish context, while African swine fever and foot and mouth disease were ranked top of the exotic diseases/conditions by the stakeholders. The study showed that for most of the diseases/conditions examined in the prioritisation exercise, the respondents indicated a preference for a combination of active and passive surveillance activities. Future extensions of the tool could include prioritisation on a per species basis.as s